Stress and welfare in ornamental fishes: what can be learned from aquaculture? - C. H. Stevens; D. P. Croft; G. C. Paull; C. R. Tyler (Journal of Fish Biology, 2017)
The ornamental fish trade is estimated to handle up to 1·5 billion fishes. Transportation and handling of fishes imposes a range of stressors that can result in mortality at rates of up to 73%. These rates vary hugely, however, and can be as low as 2%, because they are generally estimated rather than based on experimental work. Given the numbers of ornamental fishes traded, any of the estimated mortality rates potentially incur significant financial losses and serious welfare issues. Industry bodies, such as the Ornamental Aquatic Trade Association (OATA), have established standards and codes of best practice for handling fishes, but little scientific research has been conducted to understand the links between stress, health and welfare in ornamental species. In aquaculture, many of the same stressors occur as those in the ornamental trade, including poor water quality, handling, transportation, confinement, poor social and physical environment and disease and in this sector directed research and some resulting interventions have resulted in improved welfare standards. This review considers the concept of welfare in fishes and evaluates reported rates of mortality in the ornamental trade. It assesses how the stress response can be quantified and used as a welfare indicator in fishes. It then analyses whether lessons from aquaculture can be usefully applied to the ornamental fish industry to improve welfare. Finally, this analysis is used to suggest how future research might be directed to help improve welfare in the ornamental trade.